Characterisation of the charging up effect in resistive Micromegas detectors. (April 2020) - Samarati, J; Iengo, P; Longo, L; Sekhniaidze, G; Sidiropoulou, O; Wotschack, J
Abstract: During the last decade, a major improvement in the field of the Micro-Pattern Gaseous Detectors has been reached by adding a layer of resistive strips above the readout strips to reduce drastically the effect of discharges. The resistive strips are separated from the readout strips by a thin layer of insulator. When the detector is operated some gain reduction is observed over the first seconds or minutes after switch-on, stabilising after some time. Is this related to the presence of the insulator or are there other mechanisms at work? We report here the results of a detailed study of this effect and compare resistive-strip and Diamond Like Carbon (DLC) Micromegas detectors. We will present and quantify the main characteristics of this effect, i.e, the relative gain drop and the time to reach a stable regime, as a function of the detector configuration and rate. In addition we studied the influence of the pillars that support the mesh on the behaviour of bulk and non-bulk Micromegas detectors.